O Ensino De Geografia No Pibid: Relatos De Experiências Na Escola Estadual Dr. Pedro Ludovico Teixeira Porto Nacional - To - REIS, Wanderson Dias Dos (Universidade Federal do Tocantins, 2023)
This report refers to the activities and studies developed by the Institutional Scholarship Program for Teaching Initiation (Pibid) of the Federal University of Tocantins (UFT), Porto Nacional-TO campus, at state College Doctor Pedro Ludovico Teixeira. The objective of the action was to support pedagogical actions related to the theory and practice of teaching/learning geography. Passing on experiences obtained during the project to enhance the training of undergraduate students. Our meetings took place weekly for the elaboration and development of workshops, with students, supervisors and coordinator, in order to reach a fixed point of content. The workshops were aimed at providing students with an understanding of the season of the year and the movement of the earth around the sun, understanding when each season of the year occurs and the importance of each season for nature and the human being. In this way, make the students have a mental elaboration of each one of them.